Study on thermal stability and degradation kinetics of bio-based low-density polyethylene - Aniśko, Joanna; Sałasińska, Kamila; Barczewski, Mateusz (Polimery, 2023)
The degradation kinetics of low-density bio-based polyethylene three grades were examined using the TGA method in nitrogen and air atmosphere. An analysis of gases produced during thermal decomposition in air was also performed. The mechanism of thermal degradation processes of biobased polyethylene was proposed in relation to literature data on the thermal decomposition of polyethylene of petrochemical origin.